Photon-axion Conversion Cross-sections in a Resonant Cavity with \(TM_m10\) Mode - Thuy, Dao Thi Le; Thuc, Le Nhu; Soa, Dang Van (Communications in Physics, 2012)
Photon-axion conversions in the resonant cavity with the mode \((TM_m10)\) are considered in detail. The differential cross-sections and numerical evaluations are presented. It is shown that there is a resonant conversion for the considered process at low energies, in which the conversion cross-sections are much larger than those of the wave guide in the same conditions. Some estimates for experimental conditions are given from our results.